(untitled) (Nativa, 2024)
ABSTRACT: Medicinal plants, such as mint, contain active ingredients, which, although they are responsible for the therapeutic properties attributed to them, are also responsible for poisoning and adverse reactions that can occur if they are used in inadequate doses, high doses, or for prolonged periods. Many of these plant species have survived for millions of years thanks to their ability to produce substances that protect them from predators or extreme conditions. Even though some of these compounds (condensed tannins, phenols, alkaloids, oligosaccharides, and saponins) can produce a violent and immediate reaction, in most cases, they have a subtle effect that manifests itself with prolonged ingestion. By applying computational chemistry, the structures of bioactive molecules were revealed, representing them three-dimensionally after virtual screening. Therefore, in the project’s development, the effect of water stress on the production of flavonoids in the protected mint crop was studied, using the previously measured field capacity and ultimately controlling the irrigation. This was divided into four irrigation application treatments (each 3, 6, 9, and 12 days), evaluating different agronomic variables and through a foliar analysis of the content of flavonoids present in the four treatments under study. The findings of this study, with their significant implications for medicinal plant cultivation, underscore how water stress can affect the production of flavonoids in mint. This knowledge can be directly applied to optimize cultivation practices and enhance the quality of medicinal plants, thereby benefiting the agricultural and pharmaceutical industries. Keywords: aromatic plants; computational chemistry; computational chemical structural study; secondary metabolites. Efeito do estresse hídrico no crecimento vegetativo e na concentração foliar de flavonoides em hortelã (mentha x piperita) sob condições de cultivo protegido RESUMO: As plantas medicinais, como a hortelã, contêm princípios ativos que, embora sejam responsáveis ​​pelas propriedades terapêuticas que lhes são atribuídas, são também responsáveis ​​por intoxicações e reações adversas que podem ocorrer se forem utilizadas em doses inadequadas, em doses elevadas ou por períodos prolongados. períodos. Muitas destas espécies de plantas sobreviveram durante milhões de anos graças à sua capacidade de produzir substâncias que as protegem de predadores ou de condições extremas. Embora alguns destes compostos (taninos condensados, fenóis, alcalóides, oligossacarídeos e saponinas) possam produzir uma reação violenta e imediata, na maioria dos casos, eles têm um efeito sutil que se manifesta com a ingestão prolongada. Através da aplicação da química computacional, foram reveladas as estruturas das moléculas bioativas, representando-as tridimensionalmente após triagem virtual. Portanto, no desenvolvimento do projeto foi estudado o efeito do estresse hídrico na produção de flavonóides na cultura protegida de hortelã, utilizando a capacidade de campo previamente medida, e em última instância controlando a irrigação. Este foi dividido em quatro tratamentos de aplicação de irrigação (cada um com 3, 6, 9 e 12 dias), avaliando diferentes variáveis ​​agronômicas e através de uma análise foliar o teor de flavonóides presentes nos quatro tratamentos em estudo. Palavras-chave: plantas aromáticas; química computacional; estudo estrutural químico computacional; metalólitos secundários.